2010
DOI: 10.1152/ajpendo.00421.2009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cardiac mTOR/p70S6K pathway by leucine requires PDK1 and correlates with PRAS40 phosphorylation

Abstract: Like insulin, leucine stimulates the mammalian target of rapamycin (mTOR)/p70 ribosomal S6 kinase (p70S6K) axis in various organs. Insulin proceeds via the canonical association of phosphatidylinositol 3-kinase (PI3K), phosphoinositide-dependent protein kinase-1 (PDK1), and protein kinase B (PKB/Akt). The signaling involved in leucine effect, although known to implicate a PI3K mechanism independent of PKB/Akt, is more poorly understood. In this study, we investigated whether PDK1 could also participate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 57 publications
5
36
1
2
Order By: Relevance
“…At the end of the procedure, the hearts were immediately freeze clamped in liquid nitrogen and stored at Ϫ80°C. Frozen hearts were homogenized at 4°C in 9 volumes (vol/wt) of homogenization buffer that contained phosphatases and protease inhibitors (34,45). Supernatants were stored at Ϫ80°C after centrifugation (10,000 g, 30 min, 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the procedure, the hearts were immediately freeze clamped in liquid nitrogen and stored at Ϫ80°C. Frozen hearts were homogenized at 4°C in 9 volumes (vol/wt) of homogenization buffer that contained phosphatases and protease inhibitors (34,45). Supernatants were stored at Ϫ80°C after centrifugation (10,000 g, 30 min, 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…80 g/ml cycloheximide was added, and cells were harvested at each time point (0, 1,3,8,24, and 32 h). PDPK1 protein was detected on Western blot by using anti-PDPK1 (Santa Cruz Biotechnology, sc-17765), and the amount of PDPK1 protein was densitometrically analyzed using anti-GAPDH (Millipore, MAB374) as loading control.…”
Section: Methodsmentioning
confidence: 99%
“…These control loops for mTOR signaling are further potentiated by the synergistic influence of the MID1 protein complex on the protein synthesis of PDPK-1. PDPK-1 is an efficient mTOR agonist inducing mTOR activity in two different manners, directly in a leucine-dependent way and indirectly via the activation of Akt (23,24). By stimulating PDPK-1 protein synthesis, MID1 is therefore further increasing mTOR signaling.…”
Section: Mid1 Protein Complex Regulates Protein Translation In An Mtomentioning
confidence: 99%
“…Furthermore, we found that the abundance of Deptor, an inhibitor of both mTORC1 and mTORC2 (65), was suppressed by leucine administration. However, leucine pulses had no effect on the abundance or phosphorylation of PRAS40, a specific inhibitor of mTORC1 (81), although others have reported that leucine administration in rodents enhances PRAS40 phosphorylation in skeletal (45) and cardiac muscles (68).…”
Section: E710 Leucine Pulses Increase Lean Gain In Neonatesmentioning
confidence: 99%